1970
DOI: 10.1128/jb.104.1.63-68.1970
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Fatty Acids of Pathogenic Neisseria

Abstract: The cellular fatty acid composition of 20 isolates of Neisseria gonorrhoeae and 21 isolates of N. meningitidis was examined by gas-liquid chromatography. Each isolate of the two species possessed similar fatty acid profiles which were characterized by five major acids, accounting for 80 to 85% of the total. The three most abundant acids in each species were palmitic, palmitoleic, and f3-hydroxylauric acids; lauric and myristic acids were the next most abundant. The presence of large amounts of f3-hydroxylauric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…The pathogenic Neisseria spp. contain large amounts of C16:0, C16:1, C12:0, 30HC12:0, and C14:0 (107). In contrast to Moss et al (107), who reported essentially identical patterns of CFAs in N. gonorrhoeae and N. meningitidis, Jantzen et al (66) presented a numerical analysis of data that suggests that minor quantitative differences may be sufficient to reliably distinguish N. gonorrhoeae and N.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…The pathogenic Neisseria spp. contain large amounts of C16:0, C16:1, C12:0, 30HC12:0, and C14:0 (107). In contrast to Moss et al (107), who reported essentially identical patterns of CFAs in N. gonorrhoeae and N. meningitidis, Jantzen et al (66) presented a numerical analysis of data that suggests that minor quantitative differences may be sufficient to reliably distinguish N. gonorrhoeae and N.…”
Section: Identification To Genus or Speciesmentioning
confidence: 99%
“…Moss et al (24) have reported a definitive analysis of the fatty acid composition of N. meningitidis and N. gonorrhoeae. Subsequently, Lambert et al (18) described the fatty acid composition of a number of nonpathogenic Neisseria species.…”
mentioning
confidence: 99%
“…Cultivation of cells. GCBDS plates were inoculated by loop and incubated for 18 to 24 h in a candle jar at 35 C. Subinoculations were made from these plates to either solid medium (GCBDS plates) or liquid medium. The liquid media employed in this study were designated (i) LGCBDS (which consisted of: proteose peptone no.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, we have used gas-liquid chromatography, mass spectrometry, and associated analytical techniques to study the chemical composition and metabolic activity of microorganisms as a basis for their identification and classification. Chemical data from cellular fatty acids, isoprenoid quinones, sphingolipids, and cell wall amino acids have provided valuable information for the recognition of genus, species, and unclassified groups of various bacteria (3)(4)(5)(6)(7). Over the years, we have determined the fatty acid composition of all organisms currently included in the family Neisseriaceae by Bovre (1) except Kingella species (6,7).…”
mentioning
confidence: 99%